Impact of Liquidity and Solvency Ratios on Financial Performance: A Comprehensive Analysis - Haldane Blessing; Gryglewicz Sakouvogui (Institute of Accounting Research and Novation (IARN), 2023)
This research delves into the critical analysis of liquidity and solvency ratios and their profound impact on a company's financial performance. The study seeks to explore the relationship between these ratios and their influence on short-term liquidity and long-term solvency, ultimately contributing to decision-making processes for businesses and investors. Through a quantitative approach and cross-sectional design, the research evaluates data sourced from financial statements, annual reports, and databases. It employs statistical techniques, including correlation analysis and regression models, to interpret the relationships between liquidity and solvency ratios and financial indicators. The research also uncovers industry-specific variations in these ratios to provide tailored insights for various sectors. The findings highlight the significance of these ratios in assessing a company's financial health. Strong liquidity ratios, such as the current and quick ratios, were associated with improved short-term financial stability. Simultaneously, lower debt-to-equity ratios and higher interest coverage ratios signaled stronger long-term financial stability. These interrelated ratios were crucial for both businesses and investors, guiding strategic financial planning, risk management, and investment decisions. The practical implications of these findings demonstrate the significance of maintaining balanced liquidity and solvency positions. These insights provide practical guidance for businesses in formulating financial strategies, managing risks, and enhancing investor confidence. For investors, the findings empower more informed decision-making, fostering risk assessment and portfolio diversification. Overall, this research contributes significantly to the field of financial analysis, offering practical implications for businesses and investors. The implications of liquidity and solvency ratios are instrumental in shaping the financial landscape, allowing for more informed, resilient, and strategic decision-making processes for stakeholders in the financial sphere.